ApWD40a, a Member of the WD40-Repeat Protein Family, Is Crucial for Fungal Development, Toxin Synthesis, and Pathogenicity in the Ginseng Alternaria Leaf Blight Fungus Alternaria panax - Jinling Lan; Shengjie Mei; Yingxue Du; Meili Chi; Jiayi Yang; Shuliu Guo; Mingliang Chu; Ronglin He; Jie Gao (Journal of Fungi)
Alternaria panax, the primary pathogen that causes ginseng Alternaria leaf blight disease, can lead to a 20–30% reduction in ginseng yield. WD40 repeat-containing proteins are evolutionarily conserved proteins with diverse functions between different organisms. In this study, we characterized the roles of a WD40 repeat-containing protein in A. panax. The deletion of ApWD40a impaired the mycelial growth, reduced the sporulation, and significantly decreased the efficiency in utilizing various carbon sources. The ΔApwd40a mutant showed increased sensitivity to osmotic stress and metal ion stress induced by sorbitol, NaCl, and KCl, but decreased the sensitivity to a cell wall stress factor (SDS) and oxidative stress factors (paraquat and H2O2). Pathogenicity assays performed on detached ginseng leaves and roots revealed that the disruption of ApWD40a significantly decreased the fungal virulence through attenuating melanin and mycotoxin production by A. panax. A comparative transcriptome analysis revealed that ApWD40a was involved in many metabolic and biosynthetic processes, including amino acid metabolism, carbon metabolism, sulfate metabolic pathways, and secondary metabolite pathways. In particular, a significantly upregulated gene that encoded a sulfate permease 2 protein in ΔApwd40a, named ApSulP2, was deleted in the wild-type strain of A. panax. The deletion of ApSulP2 resulted in reduced biomass under sulfate-free conditions, demonstrating that the sulfate transport was impaired. Taken together, our findings highlight that ApWD40a played crucial roles in different biological processes and the pathogenicity of A. panax through modulating the expressions of genes involved in various primary and secondary metabolic processes.